A HISTORICAL AND POLITICAL REVIEW OF SINGAPORE'S POLICY TOWARDS THE MALAYS AND THE MUSLIMS - Pratama, Fikri Surya; Erasiah, Erasiah; Fitri, Anggi Meydel; Yelni, Aletri (The Ministry of Religious Affairs, The Republic of Indonesia, 2023)
When examining the condition of minorities around the world, we must pay attention to several factors such as their history, geopolitics, level of community development, patterns of integration, and the ideological style of the state in its policies. This journal article examines how Singapore's political policies towards the Malays and Muslims as minority groups. The research method used is the historical research method where data collection is done using literature review techniques. This research data analysis uses a political history approach to analyse Singapore's political policies in empowering religious communities in a secular state. The results show that Singapore has a vigilant and pragmatic attitude in making state policies in relation to Malay and Islam. This is due to its diverse demographics, its geopolitics flanked by Malaysia and Indonesia, and its past history of inter-ethnic conflict. In its development, the Singapore government has chosen the path of accommodation in making policies related to Muslims and Malays. Islam is realised as a benchmark for Singapore's domestic and foreign policies.